2022
DOI: 10.1107/s2052252522000665
|View full text |Cite
|
Sign up to set email alerts
|

Trends in coordination of rhenium organometallic complexes in the Protein Data Bank

Abstract: Radiopharmaceutical development has similar overall characteristics to any biomedical drug development requiring a compound's stability, aqueous solubility and selectivity to a specific disease site. However, organometallic complexes containing 188/186Re or 99mTc involve a d-block transition-metal radioactive isotope and therefore bring additional factors such as metal oxidation states, isotope purity and half life into play. This topical review is focused on the development of radiopharmaceuticals containing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 96 publications
0
6
0
Order By: Relevance
“…The occupancy value of the Re bound to the His15 residue however remains the highest and is on this basis preferred to those of the aspartic acid residues. A review of reported rhenium-bound protein structures in the PDB indicated that rhenium, irrespective of oxidation state or chemical formula, has a preference for histidine coordination across a range of different proteins (Brink et al, 2022). However, note that chemical kinetic studies under non-biological conditions indicate that Re-substitution rates and water-exchange rates are found to be slightly dependant on the nature of the incoming ligand, with the softer S-bonded ligands coordinating faster than N-bonded followed by O-bonded ligands to the rhenium metal centre (Salignac et al, 2003;Grundler et al, 2006).…”
Section: Additional Rhenium Atom Positionsmentioning
confidence: 99%
See 1 more Smart Citation
“…The occupancy value of the Re bound to the His15 residue however remains the highest and is on this basis preferred to those of the aspartic acid residues. A review of reported rhenium-bound protein structures in the PDB indicated that rhenium, irrespective of oxidation state or chemical formula, has a preference for histidine coordination across a range of different proteins (Brink et al, 2022). However, note that chemical kinetic studies under non-biological conditions indicate that Re-substitution rates and water-exchange rates are found to be slightly dependant on the nature of the incoming ligand, with the softer S-bonded ligands coordinating faster than N-bonded followed by O-bonded ligands to the rhenium metal centre (Salignac et al, 2003;Grundler et al, 2006).…”
Section: Additional Rhenium Atom Positionsmentioning
confidence: 99%
“…To circumvent this, the addition of an excess of imidazole was explored to assist in the crystallization. This arose on reviewing the crystallization conditions of all rhenium-protein structures listed in the Worldwide Protein Data Bank (wwPDB) (Burley et al, 2019;Brink et al, 2022). We noted that for many of the structures, where rhenium bound covalently to histidine, imidazole was present in the crystallization media.…”
Section: Introductionmentioning
confidence: 99%
“…As an example, crystallography contributed to understanding the COVID-19 pandemic through its COVID-19 viral protein structures. These aspects of interoperability are discussed in more detail by Brink et al (2024) in a companion article in this IUCr 75th Committee on Data special issue.…”
Section: The Same Report Also Statesmentioning
confidence: 99%
“…Being a full day, it complemented the main Congress microsymposium entitled 'Raw diffraction data reuse: warts and all'. A second microsymposium of the Committee on Data as principal proposer was entitled 'Interoperability of Data and Databases' (Brink et al, 2024). We also secured a Congress keynote presented by Andy Go ¨tz of ESRF on the 'European Photon and Neutron Open Science Cloud', this being the world leading effort of this consortium of more than ten European synchrotron, neutron and X-ray laser radiation sources with raw data management and sharing.…”
Section: Introductionmentioning
confidence: 99%
“…An intriguing example is recent work by Takiguchi et al who devised a deep learning model to determine which of 20000 metal complexes extracted from the Cambridge Structural Database (CSD) are single-molecule magnets (SMM) with 70% accuracy (Takiguchi et al, 2024). The latter article highlights the enormous value the CSD (Ferrence et al, 2023) and other databases offer so it is encouraging to see the work being done by CODATA to ensure the interoperability of crystallographic data within the FAIR principles (findable, accessible, interoperable and reusable) (Brink et al, 2024).…”
mentioning
confidence: 99%